Optical, elastic, electrical, and radiation shielding properties of xBaF2-(50-x)CaF2-50B203 mixed alkaline earth borate glasses / Noor Fadhilah Muhamad Sahapini - Muhamad Sahapini, Noor Fadhilah (2024)
Borate glass with fluoride ions has diverse applications in solar energy converters, lasers, infrared fibre optics, and electronic devices. Exploring the mixed alkali effect in borate glass is crucial for identify its potential. Therefore, this study aims to investigate the optical, elastic, electrical, and radiation shielding properties of xBaF2–(50 – x)CaF250B2O3 (x = 5 – 35 mol%) mixed alkaline earth borate glass. Glass samples were synthesised via melt-quenching technique, confirmed as amorphous through X-ray diffraction (XRD) analysis. FTIR spectroscopy revealed BO3 conversion to B4 units. The addition of BaF2 increased molar volume (Vm) and density (ρ) except at 25 mol% BaF2, due to mixed alkaline earth effect (MAEE) and extensive non bridging oxygen (NBO) formation, supported by the abrupt decrease of N4. The increase in the optical band gap (Eopt), describing the weakening of the glass structure. Anomaly at 20 mol% BaF2 in refractive index (n) and optical band gap (Eopt) variation, linked to the role of MAEE. The elastic velocities, shear (S) and young (Y) modulus decreased with (x ≤ 30 mol%), aligned with structural findings. However, the longitudinal (L) and bulk (Ke) modulus had minima at 10 and 25 mol%, coincided with Urbach Energy (Eu) maxima, indicating increased in structural randomness. Makishima-Mackenzie Model aligned with the experimental values, exhibiting a sudden drop at 25 mol%, due to dissociation bond energy decrease. Bulk compression model proposed isotropic deformation, affecting network bond lengths and sizes while keeping interatomic bond angles unchanged. The ring deformation model indicated isotropic ring compression due to bending between structural units. The anomaly at 25 mol% correlated with the variation of σDC against composition. The conductivity initially decreased (x < 20 mol%) due to the blocking effects of larger Ba2+ ions against Ca2+. However, an abrupt increase occurred at 25 mol%, indicating enhanced charge mobility. The temperature and frequency dependence of σAC suggested the Overlapping Large Polaron Tunneling (OLPT) model dominated as the main transport mechanism. Besides, the dielectric constant (ε') was more prominent in low-frequency regions, signifying that the space charge polarisation as main polarisation. Anomalies at 10 mol% and 25 mol% on ε', supported the elastic data. In the radiation shielding study, adding BaF2 to the glass samples increased the effective atomic number, thereby enhancing their potential for radiation attenuation. Among the various glass samples, the composition containing 25 mol% BaF2 displayed the smallest values for MFP and HVL, indicating its superior effectiveness in photon attenuation. Therefore, this composition can be considered as a preferable option among the glass samples for gamma protection applications.